Antibacterial and Antifungal Effect of 405 nm Monochromatic Laser on Endodontopathogenic Microorganisms - Takahiro Imamura; Seiko Tatehara; Yusuke Takebe; Reiko Tokuyama; Tomoko Ohshima; Nobuko Maeda; Kazuhito Satomura (International Journal of Photoenergy, 2014)
The purpose of this study is to evaluate the usefulness of 405 nm monochromatic laser irradiation as an alternative management for prevention and/or treatment of endodontic infections. A monochromatic laser-emitting device equipped with a 405-nm laser diode was developed. Using this device, the effect of 405 nm laser irradiation on the growth of Porphyromonas gingivalis, Prevotella intermedia, Enterococcus faecalis, and Candida albicans, which are microorganisms associated with persistent endodontic infections, was evaluated by viable colony counting. As a result, the irradiation with a 405 nm laser had a significant bactericidal/fungicidal effect on P. gingivalis, P. intermedia, and C. albicans, whereas the growth of E. faecalis was not affected by the irradiation. The inhibition rate in P. gingivalis and P. intermedia was ~60% and ~80%, respectively, following irradiation at 0.2 W for 300 sec. The inhibition rate in C. albicans was ~90% following irradiation at 0.2 W for 1200 sec. These results indicate that 405 nm monochromatic laser irradiation exerts a bactericidal/fungicidal effect on these microorganisms. The present study clearly demonstrates that 405 nm laser irradiation is a promising alternative management strategy for prevention and/or treatment of endodontic infections.